Isolation and Characterization of Photosensitive Hemolytic Toxins from the Mixotrophic Dinoflagellate Akashiwo sanguinea - Jiling Pan; Ting Fang; Shuang Xie; Ning Xu; Ping Zhong (Marine Drugs)
The mixotrophic dinoflagellate Akashiwo sanguinea is known to have acute toxic effects on multiple marine organisms, while the composition and chemical properties of its toxins remain unclear. In this study, we established a method for separation and purification of A. sanguinea toxins using chromatographic techniques. The acetone extract of A. sanguinea exhibited higher hemolytic activity and shorter incubation time compared to methanol and ethyl acetate extracts. Five fractions were obtained by solid-phase extraction (SPE), of which SPE3 (acetone/water ratio 3:2) and SPE4 (acetone/water ratio 4:1) exhibited the highest hemolytic activities and allelopathic effects. Further purification on SPE3 and SPE4 using reverse-phase high-performance liquid chromatography (RP-HPLC) coupled with a diode array detector (DAD) resulted in 11 subfractions, among which Fr4-5 displayed the strongest hemolytic activity. Nearly all active subfractions exhibited higher hemolytic activities incubated under light than those in the dark (p < 0.05), suggesting that A. sanguinea can produce both photosensitive and non-photosensitive toxins, with the former being the primary contributors to its hemolytic activity. Molecular characterization by UV-Vis, FTIR, and HRMS/MS analysis revealed that the structural features of Fr4-5 were highly consistent with porphyrin analogs and could be derived from chlorophyll c-related precursors. These findings highlight that the photosensitive toxins in A. sanguinea may serve dual roles in stress adaptation and ecological competition, potentially contributing to the formation of the blooms.